Avaliação da altura da canaleta de braquetes dos incisivos na prescrição de roth - Mattar, Carolina (2011)
This study evaluated the accuracy of slot’s height of 360incisorbrackets. Those brackets arewith.022” Roth prescription, produced by commercial brands Abzil, GAC, Morelli, Ormco, RMO and Unitek. The aim of this study was to determine whether slot’s height was in accordance with those prescribed by the author and to compare the actual slot’s height found among the six brands studied. The images of the brackets were obtained from a Scanning Electron Microscope(SEM) and measuredbyAutoCAD2011.The results were analyzed by parametric ANOVA, and tested by Shapiro Wilk and Levene test, which showed P >0.05, so it is not significant at5%. When the brackets were comparing among the brands, it was used Tukey HSD test. The tolerance of slot’s height was 0.56mmto0.60mmaccording toDIN13971and13971-2. When the brackets were comparingamong the brands, the upper incisors formed two main groups (Morelli and Ormco) with the slot sizes statistically superior height and another group (Abzil, GAC, Rocky and Unitek) similar but with smaller sizes. In relation to the brackets of the upper lateral incisors, the order of decreasing slot’s height was followed by Ormco after Morelli, and then the other brands Unitek, Abzil, GAC and Rocky.The brackets of the lower incisors were divided into two groups following descending order: Morelli, Ormco and Rocky and after Abzil, Unitek and GAC. The whole sample showed that the slot’s height was smaller when compared with the prescription and below the tolerance given by DIN. It is hoped that further research involving orthodontic materials are made so that the awareness of the accuracy of the dimensions of the brackets accentuates for the orthodontists as to manufacturers.